Low‐dose thymoglobulin for prevention of chronic graft‐versus‐host disease in transplantation from an HLA‐matched sibling donor - Cho, Byung‐Sik; Min, Gi‐June; Park, Sung‐Soo; Yoon, Seok Yoon; Park, Silvia; Jeon, Young‐Woo; Shin, Seung‐Hwan; Yahng, Seung‐Ah; Yoon, Jae‐Ho; Lee, Sung‐Eun; Eom, Ki‐Seong; Kim, Yoo‐Jin; et al. (American journal of hematology, 2021)
Despite the proven efficacy of anti‐T‐cell or antithymocyte globulin (ATG) for chronic graft‐versus‐host disease (GVHD) prevention in transplantation from an unrelated donor, dosing protocols and the effects of ATG on relapse and infection remain controversial. In the setting of transplantation from an HLA‐matched sibling (MSD‐T), few randomized studies have been conducted. We conducted a prospective, single‐center, open‐label, randomized study of low‐dose thymoglobulin (2.5 mg/kg) for chronic GVHD prevention. A total of 120 patients with acute leukemia were randomly assigned in a 1:1 ratio. After a median follow‐up of 27 months, the cumulative incidence of chronic GVHD in the ATG and non‐ATG groups was 25.0% and 65.4% (p < 0.001), respectively. The ATG group had an increased relapse rate compared with the non‐ATG‐group (20.0% vs. 9.3%; p = 0.055), with risks that differed according to cytogenetic subgroup (high‐risk, 29.6% vs. 9.3%, p = 0.042; non‐high‐risk, 12.2% vs. 9.2%, p = 0.596). Chronic GVHD‐free and relapse‐free survival (cGRFS) was higher in the ATG group (46.7% vs. 19.4%; p = 0.070), and the difference was significant in a cytogenetic non‐high‐risk subgroup (45.5% vs. 0%; p = 0.038). No differences were observed in other survival outcomes. Improved physical components in quality‐of‐life scores were observed in the ATG group at 12 months after transplantation. A higher rate of Epstein–Barr virus reactivation was observed in the ATG group (21.8% vs. 5.1%; p = 0.013), whereas no between‐group differences for other complications. In conclusion, the low‐dose thymoglobulin effectively prevented chronic GVHD in MSD‐T, resulting in improvement in quality‐of‐life and cGRFS, whereas the necessity of caution for high‐risk acute leukemia.